A Behavioral Explanation for Normal Wage Rigidity During the Great Depression - O'Brien, Anthony Patrick (Quarterly Journal of Economics, 1989)
Nominal wages in manufacturing were left unchanged by the large decline in nominal demand that marked the first two years of the Great Depression. This rigidity in nominal wages is explained using the tools of the behavioral theory of the firm. The emphasis is on the reasons firms changed their decision rules linking fluctuations in final sales to changes in nominal wages.